Demographics and management of outpatient concussion visits among neurologists and non-neurologists: 2006–2016 - Patrick D Asselin; Rebekah Mannix (Concussion)
Aim: Describe the patient demographics and management of outpatient concussion visits, focusing on neurologists. Materials & methods: We used the National Ambulatory Medical Care Survey to provide ...